Positive electrode material and preparation method and application thereof

By doping element M and covering the coated substance containing element A in the nickel, cobalt, manganese, lithium ternary material, the problem of reducing material circulation stability is solved, better cycle stability and rate performance is achieved, and the service life of lithium-ion batteries is extended.

CN119812252APending Publication Date: 2025-04-11ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411914619.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Nickel-cobalt-manganese lithium ternary materials have problems with reduced cycle stability in lithium-ion batteries, mainly due to instability in surface structure and degradation of transition metal elements.

Method used

The interlayer spacing and grain refinement of the matrix material is enhanced by doping element M (such as Mg, B, Al, Ga, Fe, Sb, Zr, Ru, Nb, Mo, Eu, Cu, Pb, S or F), and the interface side reaction is reduced and interface stability is enhanced by covering the coated substance containing element A (such as Mg, B, Al, Ti, La, Y or Zr).

Benefits of technology

Through doping and coating technology, the cycle stability and rate performance of the cathode material are improved, the diffusion capacity of lithium ions is enhanced, and the service life of lithium ion batteries is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812252A_ABST
    Figure CN119812252A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method and application thereof. The positive electrode material comprises a base material containing a doping element M, the base material is coated with a coating substance containing an element A, and the doping element M comprises at least one of Mg, B, Al, Ga, Fe, Sb, Zr, Ru, Nb, Mo, Eu, Cu, Pb, S or F; the element A comprises at least one of Mg, B, Al, Ti, La, Y or Zr. According to the invention, by doping the element M, increasing the interlayer spacing of the base material and refining grains, the diffusion of total lithium ions in the charge-discharge process of the positive electrode material is accelerated, and the electrochemical properties such as cycle stability, rate capability and the like of the positive electrode material are enhanced. A coating material containing an element A is coated and subjected to a consumption reaction with residual lithium on the surface of a matrix material to form a coating layer, so that the interface side reaction of the matrix material is reduced, the interface stability of the positive electrode material is enhanced, and the cycle performance of the positive electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a positive electrode material and a preparation method and application thereof. Background Art

[0002] Nickel-cobalt-manganese-lithium ternary materials are widely used in the field of lithium-ion batteries due to their high density, high operating voltage and reasonable cost. However, while pursuing higher energy density, nickel-cobalt-manganese-lithium ternary materials also face challenges such as reduced cycle stability. At present, nickel-cobalt-manganese-lithium ternary materials have problems such as unstable surface structure and easy degradation of transition metal elements. This is mainly because the average bond energy inside the nickel-cobalt-manganese-lithium ternary positive electrode material is lower, the surface alkalinity is higher, and it is easier to have interfacial side reactions with the electrolyte, resulting in a large amount of metal oxygen released inside the lattice during the cycle, resulting in poor material cycle performance, which in turn affects the performance of lithium-ion batteries and reduces the service life of lithium-ion batteries. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a positive electrode material, which is used in a battery, and the resulting battery has good cycle performance.

[0004] The invention also provides a method for preparing the positive electrode material.

[0005] The invention also provides a positive electrode.

[0006] The present invention also provides a secondary battery.

[0007] In a first aspect of the present invention, a positive electrode material is proposed, comprising a base material containing a doping element M, wherein the base material is coated with a coating material containing an element A, wherein the doping element M comprises at least one of Mg, B, Al, Ga, Fe, Sb, Zr, Ru, Nb, Mo, Eu, Cu, Pb, S or F; and the element A comprises at least one of Mg, B, Al, Ti, La, Y or Zr.

[0008] The positive electrode material according to the embodiment of the present invention has at least the following beneficial effects:

[0009] In the present invention, by doping the element M, the interlayer spacing of the base material is increased, the grains are refined, the diffusion of lithium ions is accelerated during the charge and discharge process of the positive electrode material, and the electrochemical properties such as the cycle stability and rate performance are enhanced. By coating with a coating material containing the element A, the residual lithium on the surface of the base material is consumed to form a coating layer, the interface side reaction of the base material is reduced, the interface stability of the positive electrode material is enhanced, and the cycle performance is improved.

[0010] In some embodiments of the present invention, the doping element M includes element M1 and element M2. Element M1 includes at least one of Mg, B, Al, Ga, Fe, Sb, Zr, Ru, Nb, Mo, or Eu. Element M2 includes at least one of Mg, B, Al, Ga, Fe, Sb, Zr, Ru, Nb, Mo, Eu, Cu, Pb, S, or F. Element M1 and element M2 are different.

[0011] In some embodiments of the present invention, element M1 includes at least one of Fe, Ru, or Eu. Element M2 includes at least one of Fe, Ru, Eu, Cu, Pb, S, or F.

[0012] In some embodiments of the present invention, element M1 is Ru and element M2 is F.

[0013] Ru doping increases the interlayer spacing of the cathode material, refines the particles, accelerates the diffusion of lithium ions, and enhances the cycling stability of the cathode material. And Ru doping is mainly at the Co position of the cathode material, which has an enhancing effect on the electronic conductivity of the material. F doping is mainly at the O position, which has the effect of stabilizing the framework structure. The co-doping of Ru and F elements realizes the coordinated doping of the Co position and the O position, synergistically strengthens and refines the particles, enhances the framework structure, and improves the electrochemical performance.

[0014] In some embodiments of the present invention, the chemical formula of the matrix material is: M α -Li β Ni x Co y Mn z O2, 0.5 ≤ x < 1, 0 < y < 1, 0 < z < 1, x + y + z = 1, 0.001 ≤ α ≤ 1, 0.80 ≤ β ≤ 1.06. Optionally, 0.90 ≤ β ≤ 1.06.

[0015] In some embodiments of the present invention, 1.0 ≤ β ≤ 1.06. Optionally, 1.03 ≤ β ≤ 1.06.

[0016] In some embodiments of the present invention, 0.5 ≤ x ≤ 0.95.

[0017] In some embodiments of the present invention, 0.05 < y < 1.

[0018] In some embodiments of the present invention, 0.05 < z < 1.

[0019] In some embodiments of the present invention, 0.005 ≤ α ≤ 0.3.

[0020] In some embodiments of the present invention, the chemical formula of the matrix material is: M1a -M2 b -Li β Ni x Co y Mn z O2, where 0.005 ≤ a ≤ 0.06, 0.002 ≤ b ≤ 0.06, 0.5 ≤ x < 1, 0 < y < 1, 0 < z < 1, x + y + z = 1, 0.80 ≤ β ≤ 1.06. Optionally, 0.010 ≤ a ≤ 0.050, 0.005 ≤ b ≤ 0.050. Optionally, 0.90 ≤ β ≤ 1.06.

[0021] In some embodiments of the present invention, the particle size of the positive electrode material is D1, and the particle size of the undoped and uncoated positive electrode material is D2, 0.3 ≤ D1 / D2 ≤ 0.9, where the chemical formula of the undoped and uncoated positive electrode material is: Li β’ Ni x’ Co y’ Mn z’ O2, 0.5 ≤ x' < 1, 0 < y' < 1, 0 < z' < 1, x' + y' + z' = 1, 0.80 ≤ β' ≤ 1.06. Optionally, 0.4 ≤ D1 / D2 ≤ 0.8. Optionally, 0.90 ≤ β' ≤ 1.06.

[0022] D1 / D2 represents the degree of grain refinement of the positive electrode material. It can be seen that in the present invention, the matrix material is doped with the doping element M and coated with the coating material containing the element A. The doping element has the effect of refining grains, and the coating can improve the uniformity of the material particles. Therefore, compared with the undoped and uncoated positive electrode material, the positive electrode material of the present invention has the effect of refining grains and better particle uniformity.

[0023] In some embodiments of the present invention, the D of the positive electrode material v90 and D v50 have a ratio of 1.1 to 1.7. D v90 and D v50 are in the unit of μm. Optionally, the ratio of D v90 to D v50 of the positive electrode material is 1.2 to 1.6, and further optionally 1.3 to 1.6. The ratio of D v90 to D v50 of the positive electrode material is used to characterize the degree of particle uniformity. The closer this ratio is to 1, the better the particle uniformity.

[0024] In some embodiments of the present invention, the D of the positive electrode material v50 is 6 to 13 μm, and can be optionally 6 to 10.5 μm.

[0025] In some embodiments of the present invention, in the positive electrode material, the coating substance includes boron oxide.

[0026] In some embodiments of the present invention, the molar ratio m of the element A to the matrix material satisfies: 0.001 ≤ m ≤ 0.1. Optionally, 0.002 ≤ m ≤ 0.1. Further optionally, 0.002 ≤ m ≤ 0.01. Specifically, it can be optionally 0.006 ≤ m ≤ 0.01.

[0027] In a second aspect of the present invention, a method for preparing a positive electrode material is provided, including the following steps:

[0028] S1, mixing a nickel-cobalt-manganese precursor, a lithium source, and an M source, and sintering to obtain a matrix material;

[0029] S2, mixing the matrix material with an A source and heating to obtain the positive electrode material.

[0030] In some embodiments of the present invention, the particle size of the positive electrode material is D1, and the particle size of the un-doped and un-coated positive electrode material is D2, where 0.3 ≤ D1 / D2 ≤ 0.9. Optionally, 0.4 ≤ D1 / D2 ≤ 0.8. Optionally, the chemical formula of the un-doped and un-coated positive electrode material is: Li β’ Ni x’ Co y’ Mn z’ O2, 0.5 ≤ x' < 1, 0 < y' < 1, 0 < z' < 1, x' + y' + z' = 1, 0.80 ≤ β' ≤ 1.06.

[0031] Among them, the un-doped and un-coated positive electrode material refers to: under the same conditions as other conditions of the method for preparing the positive electrode material of the present invention, only without adding the M source and the coating step of the A source in step S2, the obtained positive electrode material.

[0032] In some embodiments of the present invention, in step S1, the sintering step includes heating at 300 - 550 °C for 1 - 10 h first, and then heating at 600 - 860 °C for 5 - 20 h.

[0033] In some embodiments of the present invention, in step S1, the nickel-cobalt-manganese precursor is Ni x Co y Mn z (OH)2, 0.5 ≤ x < 1, 0 < y < 1, 0 < z < 1, x + y + z = 1. Optionally, 0.5 ≤ x < 1, 0.05 < y < 1, 0.05 < z < 1, x + y + z = 1.

[0034] In some embodiments of the present invention, in step S1, the mixing method includes grinding.

[0035] In some embodiments of the present invention, the lithium source includes at least one of LiOH or a hydrate of LiOH.

[0036] In some embodiments of the present invention, the M source includes at least one of a chloride of element M or a sodium of element M. Optionally, the M source is selected from at least one of a chloride of element M, a hydrate of a chloride of element M, a sodium of element M or a hydrate of a sodium of element M.

[0037] In some embodiments of the present invention, in step S1, the M source includes an M1 source and an M2 source. Optionally, the M1 source includes at least one of a chloride of element M1 or a sodium compound of element M1; the M2 source includes at least one of a chloride of element M2 or a sodium compound of element M2. Optionally, the M1 source is selected from at least one of a chloride of element M1, a hydrate of a chloride of element M1, a sodium compound of element M1, or a hydrate of a sodium compound of element M1; the M2 source is selected from at least one of a chloride of element M2, a hydrate of a chloride of element M2, a sodium compound of element M2, or a hydrate of a sodium compound of element M2.

[0038] In some embodiments of the present invention, in step S1, the nickel-cobalt-manganese precursor and the lithium source are ground evenly, and then ground evenly with the M source, and sintered to obtain a matrix material.

[0039] In some embodiments of the present invention, in step S2, the heating temperature is 120-420°C, such as optionally, the heating temperature is 200-260°C, further such as 240°C.

[0040] In some embodiments of the present invention, in step S2, the heating time is 3 to 10 hours.

[0041] In some embodiments of the present invention, in step S2, the source A includes boric acid (H3BO3). The base material is coated with boric acid at low temperature (such as coating), which can react and consume the residual lithium on the surface of the base material, and while consuming the residual lithium, a coating layer containing the B compound is formed on the surface of the base material. When used in a secondary battery, it can enhance the interface stability of the positive electrode material and reduce the occurrence of side reactions between the positive electrode material and the electrolyte.

[0042] In some embodiments of the present invention, in step S2, the molar ratio m of the element A contained in the A source to the matrix material satisfies: 0.001≤m≤0.1.

[0043] In a third aspect of the present invention, a positive electrode active layer is provided, comprising the positive electrode material. Optionally, the positive electrode active layer is prepared by using a preparation raw material comprising the positive electrode material.

[0044] In some embodiments of the present invention, the thickness of the positive electrode active layer is 10 to 100 μm, such as 30 to 70 μm, and further 45 μm, 60 μm, etc.

[0045] In some embodiments of the present invention, the positive electrode active layer further comprises a conductive agent and a binder. Optionally, the preparation raw material further comprises a conductive agent and a binder. Further optionally, the conductive agent includes but is not limited to acetylene black, etc., and the binder includes but is not limited to polyvinylidene fluoride.

[0046] In a fourth aspect of the present invention, a positive electrode is provided, comprising a positive electrode active layer or the positive electrode material mentioned above. Optionally, the positive electrode may be a positive electrode sheet.

[0047] According to a fifth aspect of the present invention, a secondary battery is provided, comprising the above-mentioned positive electrode or the above-mentioned positive electrode material.

[0048] In some embodiments of the present invention, the secondary battery comprises a lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0050] Figure 1 This is a microscopic test result diagram of the positive electrode material in Example 3 of the present invention;

[0051] Figure 2 This is a microscopic test result diagram of the positive electrode material in Comparative Example 1. DETAILED DESCRIPTION

[0052] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0053] The experimental methods in the following examples without specifying specific conditions are generally carried out according to conventional conditions in the art or conditions recommended by the manufacturers; the raw materials and reagents used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.

[0054] Example 1

[0055] This embodiment discloses a positive electrode material, the preparation process of which includes:

[0056] (I) Synthesis of the matrix material (Ru-doped NCM811), comprising: weighing appropriate amounts of Ni 0.80 Co0.10 Mn 0.10 (OH)2 precursor, lithium source LiOH·H2O, first Ni 0.80 Co 0.10 Mn 0.10 (OH)2 and LiOH·H2O are ground and mixed evenly according to n(Li) / n(Ni+Co+Mn) of 1.03, where n(Ni+Co+Mn) refers to the sum of the amounts of Ni, Co and Mn in the precursor, and then RuCl3·6H2O is weighed and added to it according to n(Ru):n(Ni+Co+Mn)=0.030:1 for grinding and mixing evenly. Heat at 490℃ for 5 hours, then heat at 780℃ for 10 hours, and cool to room temperature. The heating and cooling rate during this period is 5℃ / min. Finally, Ru-doped NCM811: Ru-doped LiNi 0.80 Co 0.10 Mn 0.10 O2 (there will be some loss of Li content during the synthesis process, so the Li element in LiOH·H2O is slightly excessive compared to that in Ru-doped NCM811).

[0057] (II) Boric acid (H3BO3) coating the substrate material, comprising: weighing an appropriate amount of substrate material (Ru-doped NCM811), and then weighing boric acid (H3BO3) and LiNi according to n(B):n(Ni+Co+Mn)=0.006:1 0.80 Co 0.10 Mn 0.10 O2 is mixed evenly, and then heated at 240°C (120-420°C) for 5h to finally obtain Ru-doped NCM811 positive electrode material coated with B substance.

[0058] This embodiment also discloses a positive electrode sheet, the preparation process of which includes: the Ru / F co-doped NCM811 positive electrode material coated with B substance prepared in this embodiment, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are fully stirred in an N-methyl methyl pyrrolidone solvent system at a mass ratio of 96.5:2.5:2. After stirring evenly, a positive electrode slurry (solid content of about 75%) is obtained, the slurry is coated on an Al foil (thickness of 15 μm), baked, rolled, and a positive electrode active layer (thickness of 60 μm) is formed on the surface of the Al foil, and strips are obtained to obtain a positive electrode sheet.

[0059] This embodiment also discloses a lithium-ion battery, including the positive electrode sheet of this embodiment, and the preparation process thereof includes:

[0060] Preparation of negative electrode sheet: Graphite, conductive agent carbon nanotube, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose are stirred and mixed in deionized water at a mass ratio of 97.2:1.4:0.7:0.7. After being mixed evenly, the negative electrode slurry is coated on Cu foil (thickness of 10 μm), baked, rolled, and a negative electrode active layer (thickness of 75 μm) is formed on the surface of the Cu foil, and then stripped to obtain a negative electrode sheet.

[0061] Preparation of isolation membrane: A polyethylene (PE) polymer film is used as the isolation membrane with a thickness of 12 μm.

[0062] Preparation of electrolyte: The organic solvents are uniformly mixed according to the mass ratio to obtain an organic solvent mixture, the detailed mass ratio is: ethylene carbonate (EC): propyl propionate (PP): vinylene carbonate (VC): diethyl carbonate (DEC): propylene carbonate (PC) = 24:18:3:28:27. Lithium salt LiPF6 is added to the organic solution, and the mass ratio of the added mass to the organic solvent is 8.5:91.5. The final solution obtained after uniform mixing is the electrolyte of the lithium ion battery.

[0063] The assembly of lithium-ion batteries includes: stacking the positive electrode sheet, the separator, and the negative electrode sheet in order, and winding them to obtain an electrode assembly. When folding the electrode sheet, pay attention to the separator to completely separate the positive and negative electrode sheets. Put the motor assembly in the packaging shell, inject the electrolyte into the packaging shell and package it, and finally obtain a lithium-ion battery.

[0064] Example 2

[0065] This embodiment discloses a positive electrode material, which is different from the embodiment 1 in that step (I) is different: step (I) in this embodiment is to synthesize F-doped NCM811: weigh appropriate amounts of Ni 0.80 Co 0.10 Mn 0.10 (OH)2 precursor, lithium source LiOH·H2O, first Ni 0.80 Co 0.10 Mn 0.10 (OH)2 and LiOH·H2O were ground and mixed evenly according to n(Li) / n(Ni+Co+Mn)=1.03, and then NaF was weighed and added according to n(F):n(Ni+Co+Mn)=0.020:1 and ground and mixed evenly. Heat at 490℃ for 5 hours, then heat at 780℃ for 10 hours, and cool to room temperature. The heating and cooling rate during this period was 5℃ / min. Finally, F-doped LiNi 0.80 Co 0.10 Mn 0.10 O2 positive electrode material, other aspects are the same as in Example 1.

[0066] This embodiment also discloses a positive electrode sheet, which is different from the embodiment 1 in that the positive electrode material in this embodiment is used to replace the positive electrode material in the embodiment 1. Other aspects are the same as the embodiment 1.

[0067] This embodiment also discloses a lithium ion battery, which is different from the embodiment 1 in that the positive electrode sheet in this embodiment is used to replace the positive electrode sheet in the embodiment 1. Other aspects are the same as the embodiment 1.

[0068] Example 3

[0069] This embodiment discloses a positive electrode material, the preparation process of which includes:

[0070] (I) Synthesis of the matrix material (Ru / F co-doped NCM811), comprising: weighing appropriate amounts of Ni 0.80 Co 0.10 Mn 0.10 (OH)2 precursor, lithium source LiOH·H2O, first Ni 0.80 Co 0.10 Mn 0.10 (OH)2 and LiOH·H2O were ground and mixed evenly according to n(Li) / n(Ni+Co+Mn) of 1.03, where n(Ni+Co+Mn) refers to the sum of the amounts of Ni, Co and Mn in the precursor, and then RuCl3·6H2O and NaF were weighed and added according to n(Ru):n(F):n(Ni+Co+Mn)=0.010:0.020:1 and ground and mixed evenly. Heat at 490°C for 5 hours, then heat at 780°C for 10 hours, and cool to room temperature. The heating and cooling rate during this period was 5°C / min. Finally, Ru / F-doped LiNi 0.80 Co 0.10 Mn 0.10 O2 (abbreviation: Ru / F co-doped NCM811).

[0071] (II) Boric acid (H3BO3) coating the substrate material, comprising: weighing an appropriate amount of substrate material (Ru / F co-doped NCM811), and then weighing boric acid (H3BO3) and LiNi according to n(B):n(Ni+Co+Mn)=0.006:1 0.80 Co 0.10 Mn 0.10 O2 is mixed evenly, and then heated at 240°C (120-420°C) for 5h to finally obtain Ru / F co-doped NCM811 positive electrode material coated with B substance.

[0072] This embodiment also discloses a positive electrode sheet, the preparation process of which includes: the Ru / F co-doped NCM811 positive electrode material coated with B substance prepared in this embodiment, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are fully stirred in an N-methyl methyl pyrrolidone solvent system at a mass ratio of 96.5:2.5:2. After stirring evenly, a positive electrode slurry is obtained, and the slurry is coated on an Al foil (thickness of 15 μm), baked, rolled, and a positive electrode active layer (thickness of 60 μm) is formed on the surface of the Al foil, and striped to obtain a positive electrode sheet.

[0073] This embodiment also discloses a lithium-ion battery, including the positive electrode sheet of this embodiment, and the preparation process thereof includes:

[0074] Preparation of negative electrode sheet: Graphite, conductive agent carbon nanotube, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose are stirred and mixed in deionized water at a mass ratio of 97.2:1.4:0.7:0.7. After being mixed evenly, the negative electrode slurry is coated on Cu foil (thickness of 10 μm), baked, rolled, and a negative electrode active layer (thickness of 75 μm) is formed on the surface of the Cu foil, and then stripped to obtain a negative electrode sheet.

[0075] Preparation of isolation membrane: A polyethylene (PE) polymer film is used as the isolation membrane with a thickness of 12 μm.

[0076] Preparation of electrolyte: The organic solvents are uniformly mixed according to the mass ratio to obtain an organic solvent mixture, the detailed mass ratio is: vinyl ester (EC): propyl propionate (PP): vinyl carbonate (VC): diethyl carbonate (DEC): propylene carbonate (PC) = 24:18:3:28:27. Lithium salt LiPF6 is added to the organic solution, and the mass ratio of the added mass to the organic solvent is 8.5:91.5. The final solution obtained after uniform mixing is the electrolyte of the lithium ion battery.

[0077] The assembly of lithium-ion batteries includes: stacking the positive electrode sheet, the separator, and the negative electrode sheet in order, and winding them to obtain an electrode assembly. When folding the electrode sheet, pay attention to the separator to completely separate the positive and negative electrode sheets. Put the motor assembly in the packaging shell, inject the electrolyte into the packaging shell and package it, and finally obtain a lithium-ion battery.

[0078] Embodiments 4 to 18

[0079] Examples 4 to 18 disclose a series of positive electrode materials, which differ from Example 3 in that the types or contents of doping elements in the positive electrode materials are different, or the ratio of the amount of B element contained in the coating layer to n(Ni+Co+Mn) is different (see Table 1 below for details), and the rest are the same as Example 3. Among them, the Eu source used for Eu doping is EuCl3·6H2O.

[0080] Embodiments 4 to 18 disclose a series of positive electrode sheets, which differ from Embodiment 3 in that the positive electrode materials in Embodiments 4 to 18 are used to replace the positive electrode materials in Embodiment 3. Other aspects are the same as in Embodiment 3.

[0081] Embodiments 4 to 18 disclose a series of lithium-ion batteries, which differ from Embodiment 3 in that the positive electrode sheets in Embodiments 4 to 18 are used to replace the positive electrode sheets in Embodiment 3. Other aspects are the same as in Embodiment 3.

[0082] Comparative Example 1

[0083] This comparative example discloses a positive electrode material, which is NCM811 positive electrode material. The preparation process includes: weighing appropriate amounts of Ni 0.80 Co 0.10 Mn 0.10 (OH)2 precursor, lithium source LiOH·H2O, first Ni 0.80 Co 0.10 Mn 0.10 (OH)2 and LiOH·H2O were ground and mixed evenly according to n(Li) / n(Ni+Co+Mn) of 1.03, and then heated at 490℃ for 5 hours and then at 780℃ for 10 hours, with the heating and cooling rate of 5℃ / min. 0.80 Co 0.10 Mn 0.10 O2 positive electrode material.

[0084] This comparative example also discloses a positive electrode sheet, which is different from Example 1 in that the positive electrode material in this comparative example is used to replace the positive electrode material in Example 1. Other aspects are the same as Example 1.

[0085] This comparative example also discloses a lithium ion battery, which is different from Example 1 in that the positive electrode sheet in this comparative example is used to replace the positive electrode sheet in Example 1. Other aspects are the same as Example 1.

[0086] Comparative Example 2

[0087] This comparative example discloses a positive electrode material, which differs from Example 2 only in that the positive electrode material in this comparative example is only F-doped LiNi 0.80 Co 0.10 Mn 0.10 O2 positive electrode material, not coated with B substance.

[0088] This comparative example also discloses a positive electrode sheet, which is different from Example 2 in that the positive electrode material in this comparative example is used to replace the positive electrode material in Example 2. Other aspects are the same as Example 2.

[0089] This comparative example also discloses a lithium ion battery, which is different from Example 2 in that the positive electrode sheet in this comparative example is used to replace the positive electrode sheet in Example 2. Other aspects are the same as Example 2.

[0090] Comparative Example 3

[0091] This comparative example discloses a positive electrode material, which differs from Example 1 only in that the positive electrode material in this comparative example is only Ru-doped LiNi 0.80 Co 0.10 Mn 0.10 O2 positive electrode material, not coated with B substance.

[0092] This comparative example also discloses a positive electrode sheet, which is different from Example 1 in that the positive electrode material in this comparative example is used to replace the positive electrode material in Example 1. Other aspects are the same as Example 1.

[0093] This comparative example also discloses a lithium ion battery, which is different from Example 1 in that the positive electrode sheet in this comparative example is used to replace the positive electrode sheet in Example 1. Other aspects are the same as Example 1.

[0094] Comparative Example 4

[0095] This comparative example discloses a positive electrode material, which is a NCM811 positive electrode material coated with a B substance. The preparation process includes: weighing an appropriate amount of Ni 0.80 Co 0.10 Mn 0.10 (OH)2 precursor, lithium source LiOH·H2O, first Ni 0.80 Co 0.10 Mn 0.10 (OH)2 and LiOH·H2O were ground and mixed evenly according to n(Li) / n(Ni+Co+Mn)=1.03, and then heated at 490℃ for 5 hours and then at 780℃ for 10 hours, with the heating and cooling rate of 5℃ / min, to obtain LiNi 0.80 Co 0.10 Mn 0.10 O2 positive electrode material. Then weigh boric acid (H3BO3) and LiNi according to n(B):n(Ni+Co+Mn)=0.006:1 0.80 Co 0.10 Mn 0.10 O2 is mixed evenly, and then heated at 240 ° C (120 ~ 420 ° C) for 5 hours to finally obtain LiNi coated with B substance 0.80 Co 0.10 Mn 0.10 O2 positive electrode material.

[0096] This comparative example also discloses a positive electrode sheet, which is different from Example 1 in that the positive electrode material in this comparative example is used to replace the positive electrode material in Example 1. Other aspects are the same as Example 1.

[0097] This comparative example also discloses a lithium ion battery, which is different from Example 1 in that the positive electrode sheet in this comparative example is used to replace the positive electrode sheet in Example 1. Other aspects are the same as Example 1.

[0098] Test example

[0099] This test example performs performance tests on the lithium-ion batteries obtained in the examples and comparative examples, specifically including:

[0100] 1) Gram capacity test:

[0101] Take 6 samples of each lithium-ion battery prepared in the embodiment and the comparative example, and charge to 4.30V under constant current and constant voltage conditions at a rate of 0.5C at room temperature. The cut-off current is 0.02C. Then, discharge at a rate of 0.5C at a constant current until the voltage is cut off at 2.5V. Record the obtained capacity, and divide the obtained capacity by the mass of the active material of the positive electrode material to obtain the gram capacity of the positive electrode material.

[0102] (2) Cyclic performance test:

[0103] Six samples of the lithium-ion batteries prepared in the embodiment and the comparative example were taken respectively, and their cycle performance was tested at 45° C. The cycle steps were respectively to repeatedly charge and discharge the lithium-ion battery, and the cycle capacity retention rate of the lithium-ion battery was calculated. When the capacity retention rate of the lithium-ion battery was lower than 80%, the cycle test was terminated, and the number of cycles was recorded.

[0104] The detailed steps are: charge to 4.30V at 3C constant current and constant voltage, the cut-off current is 0.02C, and discharge to 2.5V at 1.0C constant current. This first charge and discharge process is a cycle. Repeat this cycle step until the capacity retention rate of the lithium-ion battery is less than 70%. The cycle test is completed and the cycle number of the lithium-ion battery is recorded.

[0105] (3) Rate performance test:

[0106] Take 6 samples of each lithium-ion battery prepared in the embodiment and the comparative example, and charge to 4.30V under constant current and constant voltage conditions at a rate of 0.5C, with a cut-off current of 0.02C. Then, discharge at a constant current at a rate of 0.05C until the voltage is cut off at 2.5V. The discharge capacity at this step is S1. Charge to 4.30V under constant current and constant voltage conditions at a rate of 0.5C. The cut-off current is 0.02C. Then, discharge at a constant current at a rate of 3.0C until the voltage is cut off at 2.5V. The discharge capacity at this step is S2. The discharge capacity percentage obtained by S2 / S1*100% is the rate performance test result.

[0107] (4) SEM test of materials

[0108] The samples prepared in Example 3 and Comparative Example 1 were subjected to scanning electron microscopy (SEM, Verios 460, FEI). The SEM results are as follows: Figures 1-2 shown.

[0109] (5) Material particle size test

[0110] The positive electrode materials prepared in the embodiment and the comparative example were tested for particle size. The testing method was: GB-T19077-2016 particle size analysis laser diffraction method. The testing instrument was: Malvern MS3000+SM. v90 With D v50 The value of is processed to characterize the particle uniformity test C of the positive electrode material, C = D v90 / D v50 .

[0111] The differences in elements between the above-mentioned embodiments and comparative examples and the battery performance test results are shown in Table 1 below:

[0112] Table 1

[0113]

[0114]

[0115] Note: Grain refinement degree A = particle size D of positive electrode material v50 / Particle size D of undoped and uncoated cathode material v50 , wherein the particle size of the undoped and uncoated positive electrode material is the particle size of the positive electrode material of Comparative Example 1.

[0116] Particle uniformity C = D of positive electrode material v90 / D of positive electrode material v50 .

[0117] By comparing Examples 3 to 7, it can be seen that RuCl3·3H2O is used to dope the base material with Ru. In the range of Ru doping ratio n(Ru):n(Ni+Co+Mn) 0.01:1 to 0.05:1, as the Ru doping ratio increases, the greater the degree of particle refinement, the smaller the A value. At the same time, due to the increase in the degree of particle refinement, the uniformity of the particles has also been improved to a certain extent, and the C value has been reduced. Compared with Examples 3 to 4 and Examples 6 to 7, the particle refinement degree A value in Example 5 is 0.5, and the doping ratio of n(Ru):n(Ni+Co+Mn)=0.03:1 has the best improvement on the electrochemical properties such as gram capacity, high temperature cycle, and rate performance of the base material. Among them, because Ru doping can increase the interlayer spacing of the nickel-cobalt-manganese-lithium ternary positive electrode material, it plays a role in refining the particles, and the diffusion of lithium ions in the nickel-cobalt-manganese-lithium ternary positive electrode material can also accelerate the effect, which has a strengthening effect on the structural stability of the nickel-cobalt-manganese-lithium ternary positive electrode material and strengthens the cycle stability of the positive electrode material. Compared with n(Ru):n(Ni+Co+Mn) less than 0.01:1, when n(Ru):n(Ni+Co+Mn) is within the range of 0.01:1 to 0.05:1, the doping amount is greater, the benefits brought by Ru element doping are easier to offset the negative effects brought by Ru doping Co, and the particle refinement is better. Compared with n(Ru):n(Ni+Co+Mn) greater than 0.05:1, when n(Ru):n(Ni+Co+Mn) is within the range of 0.01:1 to 0.05:1, the Co element is not easily replaced by Ru too much, the particle refinement degree A is higher, the particle structure stability is better, and it is less likely to break during the positive electrode particle cycle, and the electrochemical performance is improved.

[0118] By comparing Example 5 and Examples 8 to 12, it can be seen that when the base material is doped with F using NaF, within the range of the F doping ratio n(F):n(Ni+Co+Mn) of 0.005:1 to 0.05:1, compared with Examples 8 to 12, the doping ratio of n(F):n(Ni+Co+Mn) of 0.02:1 in Example 5 has the best improvement on the electrochemical properties of the base material, such as gram capacity, high temperature cycle, and rate performance, and its principle is similar to the Ru doping principle.

[0119] By comparing Examples 1 to 3, it can be found that the co-doping of Ru and F elements coordinates the doping of Co and O positions, synergistically strengthens and refines the particles, enhances the skeleton structure, and improves the electrochemical performance. This is because the Ru doping is mainly at the Co position of the ternary material, which has an enhancing effect on the electronic conductivity, and the F doping is mainly at the O position, which has an effect on stabilizing the skeleton structure, increasing the interlayer spacing of the nickel-cobalt-manganese-lithium ternary positive electrode material, refining the particles, accelerating the diffusion of lithium ions, and enhancing the cycle stability of the positive electrode material.

[0120] By comparing Examples 5, 13 to 16, it can be seen that the low-temperature coating of the base material with boric acid has a great improvement in the electrochemical properties of the base material, such as the gram capacity, high-temperature cycle, and rate performance. Compared with other embodiments, the coating ratio n(B):n(Ni+Co+Mn)=0.006:1 in Example 5 has the best effect. This is because with the addition of boric acid, it will react with the surface residual lithium on the surface of the base material, eliminating the residual lithium reaction source of the positive electrode material that reacts with the electrolyte during charging and discharging. After the reaction of boric acid and residual lithium, boron-containing oxide will be generated and coated on the surface of the base material, which greatly improves the interface side reaction. And the coating process is carried out at low temperature, which can well retain the original base material structure prototype, and will not modify the surface structure of the original base material. At the same time, the particle uniformity C of the positive electrode material is also improved. The larger the coating ratio, the stronger the particle uniformity and the smaller the C value. Compared with Examples 13 to 16, the particle uniformity C in Example 5 is 1.4, and the electrochemical properties of the positive electrode material such as gram capacity, high temperature cycle, and rate performance are optimal. This is because compared with Example 5, the C values ​​in Examples 13 to 14 are higher, and the proportion of large particles in the positive electrode material is too large, while the C values ​​in Examples 15 to 16 are smaller, and the proportion of small particles is too small. Compared with 13 to 16, the ratio of large and small particles of the positive electrode material in Example 5 is optimal, and the gaps between large particles of the positive electrode material can be occupied by small particles to the maximum extent, and the contact between particles is also optimal, and its electron transfer and ion conduction performance are maximized.

[0121] By comparing Examples 1 to 18 and Comparative Examples 1 to 4, it can be found that the co-doping of MI and M2 elements (such as Ru / F co-doping) has a synergistic effect on the particle refinement of the positive electrode material and enhances the degree of refined particles A. Boron coating has a stabilizing effect on the particle uniformity C. The degree of refined particles A and particle uniformity C changed by Ru / F co-doping and boron coating have a synergistic effect on the electrochemical properties of the positive electrode material, such as gram capacity, high temperature cycle, and rate performance. This is because Ru doping and boric acid coating have different mechanisms of action, and can produce a synergistic effect in refining the grains, enhancing their lithium transport performance, and enhancing their cycle stability. B 3+ The ionic radius of Ru 3+ The ionic radius of The ionic radius of element B is smaller, and the coating is mainly to form a boron-containing oxide layer on the surface of secondary particles. The Ru element doping is mainly to preferentially occupy the incoherent crystal interface of the nickel-cobalt-manganese-lithium ternary positive electrode material. The action positions of the two elements do not conflict, and the electrochemical properties of the positive electrode material can be synergistically enhanced.

[0122] If there is no special explanation, the actual meaning of "about" in the present invention is that the error is allowed within the range of ±2%, for example, about 100 is actually 100±2%×100. The "normal temperature" and "room temperature" in the present invention, if there is no special explanation, are about 20 to 30°C. The "between" in the present invention includes the number itself, for example, "between 2 and 3" includes the endpoint values ​​2 and 3.

[0123] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A positive electrode material, characterized in that: It includes a base material containing a doping element M, and the base material is coated with a coating material containing an element A, wherein the doping element M includes at least one of Mg, B, Al, Ga, Fe, Sb, Zr, Ru, Nb, Mo, Eu, Cu, Pb, S or F; and the element A includes at least one of Mg, B, Al, Ti, La, Y or Zr.

2. The positive electrode material according to claim 1, characterized in that The doping element M includes an element M1 and an element M2, the element M1 includes at least one of Mg, B, Al, Ga, Fe, Sb, Zr, Ru, Nb, Mo or Eu, and the element M2 includes at least one of Mg, B, Al, Ga, Fe, Sb, Zr, Ru, Nb, Mo, Eu, Cu, Pb, S or F; the element M1 and the element M2 are different.

3. The positive electrode material according to claim 2, characterized in that The chemical formula of the matrix material is: M1 a -M2 b -Li β Ni x Co y Mn z O2, where 0.005≤a≤0.06, 0.002≤b≤0.06, 0.5≤x<1, 0 <y<1,0<z<1,x+y+z=1,0.80≤β≤1.06。 4. The positive electrode material according to claim 1, characterized in that The chemical formula of the matrix material is: α -Li β Ni x Co y Mn z O2, 0.5≤x<1, 0 <y<1,0<z<1,x+y+z=1,0.001≤α≤1,0.80≤β≤1.06。 5. The positive electrode material according to claim 4, characterized in that 0.5≤x≤0.95。 6. The positive electrode material according to claim 1, characterized in that The particle size of the positive electrode material is D1, the particle size of the undoped and uncoated positive electrode material is D2, 0.3≤D1 / D2≤0.9, wherein the chemical formula of the undoped and uncoated positive electrode material is: Li β’ Ni x’ Co y’ Mn z’ O2, 0.5 ≤ x' < 1, 0 <y’<1,0<z’<1,x’+y’+z’=1,0.80≤β’≤1.06。 7. The positive electrode material according to claim 1, characterized in that The positive electrode material D v90 With D v50 The ratio is 1.1 to 1.

7.

8. The positive electrode material according to claim 1, characterized in that The molar ratio m of the element A to the matrix material satisfies: 0.001≤m≤0.

1.

9. A positive electrode, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: Comprising the positive electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Doped and modified ternary positive electrode material and preparation method thereof

    CN103887483A

  • Method for preparing lithium nickel cobalt manganese oxide ternary cathode material in liquid-phase sugar coating and spray drying manners

    CN104733721A

  • High nickel anode material, preparation method thereof and lithium ion battery

    CN105070907A

  • 811-type ternary positive modified material for lithium ion batteries and preparation method thereof

    CN106711414A

  • Rare-earth element doped modified ternary high-nickel lithium battery positive electrode material and preparation method thereof

    CN108807972A